Fragmentation of land ownership in Slovakia: Evolution, context, analysis and possible solutions - Muchová, Zlatica; Raškovič, Vladimír (Land use policy, 2020)
[Display omitted] •Current state of fragmentation of property in Slovakia, its causes and evolution in time (timeline).•Negative impact of fragmentation on intended objects and measures.•Ineffectiveness of legal processes and procedural acts for fragmented ownership.•Avoidance of further fragmentation of property through legislative measures.•Possibilities of elimination of existing fragmentation from the Land Register, technical-legal synergy. Land ownership fragmentation is currently a very topical issue in Slovakia. In particular, small farmers complain that even 30 years after the end of the previous (“real socialist”) regime, there has been no significant change in the structure of agricultural land use. The subject of the article is not the land fragmentation in terms of use. In Slovakia, the problem is rather the opposite. This contribution deals with fragmentation of ownership that is mostly invisible in the landscape. Usage still dominates over the ownership and the real landowner cannot get his or her own property in a simple way. The reason for this is huge fragmentation of land ownership, which makes it virtually impossible to actually claim it. Well known solution is the land consolidation that does not advance at a rate that would guarantee the rights (and obligations) of all owners in the foreseeable future in Slovakia. Neglecting the land fragmentation by authorities leads to tense situations between landowners and land tenants and also co-causes a stagnation of rural development and issues with landscape protection. The paper describes the specific state of land ownership in Slovakia and attempts to explain this complicated situation on a sample of 50 historical and modern ownership documents. This contribution has the ambition to specify the largely yet unresolved problems that arise from the current state of massive fragmentation of land ownership. The aim of the paper is also to fill in the information gap on the topic, not only in the national context.